The loss of GLUT2 expression by glucose-unresponsive beta cells of db/db mice is reversible and is induced by the diabetic environment. - Thorens, B; Wu, Y J; Leahy, J L; Weir, G C (The Journal of Clinical Investigation, 1992)
Glucose-induced insulin secretion by beta cells of diabetic db/db mice was studied by a pancreas perfusion technique, and the levels of GLUT2 protein in pancreatic islets were assessed by immunofluorescence microscopy and protein blot analysis. Beta cells from diabetic mice had a high basal rate of insulin secretion; they did not respond to glucose stimulation but displayed a normal secretory response to arginine. At the same time, GLUT2 expression by db/db islets was lost whereas beta cells from nondiabetic db/+ mice expressed high levels of this transporter. GLUT2 levels in liver or kidney of diabetic mice were, however, mostly unaltered. Transplanting islets from db/db mice under the kidney capsule of db/+ mice restored normal GLUT2 levels. Conversely, transplantation of db/+ islets into db/db mice induced the disappearance of GLUT2 expression. When islets from db/+ mice were transplanted under the kidney capsule of streptozocin-diabetic mice, the immunodetection of GLUT2 also disappeared. We conclude that: (a) GLUT2 expression is decreased in glucose-unresponsive beta cells from db/db mice; (b) the decreased expression of GLUT2 is reversible; (c) the loss of GLUT2 expression is induced by the diabetic environment of db/db and streptozocin-induced diabetic mice. These observations together with previously published data suggest that a factor different from glucose or insulin regulates the beta cell expression of GLUT2. Images